If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13y + x = 66 Reorder the terms: x + 13y = 66 Solving x + 13y = 66 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13y' to each side of the equation. x + 13y + -13y = 66 + -13y Combine like terms: 13y + -13y = 0 x + 0 = 66 + -13y x = 66 + -13y Simplifying x = 66 + -13y
| 4v/10 | | -3(x-4)=24 | | y=0x-6 | | 2m^2+80m=0 | | X+2=2.10 | | tan(40=3/x | | 7.5-2n=-2 | | 9-8x=-4-8x | | x-3/15x6x-18/5x | | -2a=10+(-7) | | cosx+sinx=2x | | x^2-48x=-104 | | 2(6x^2+11)=0 | | 7.68=3x | | ((400-2x)/2)x | | 9u^2-162u=0 | | 3x^2-6x+21=0 | | 12x^2=22 | | 88=r-92 | | -28=-4n-4 | | (400-2x/2)x | | 2(2x+4)=2(x+2) | | (y/18)-(y/6)=(4y/3) | | 8n-4n+n+18=5(n+3) | | 43=y-93 | | ((((4x^-5)u)/(z^-4)))^3)*(x^4z^-3) | | 47+(-1)x=46 | | (-2x+3y-4z)+(-5x+10y)= | | 46+(4x+2)=90 | | 2(x+3)-4(5-x)=110 | | 29+(-1)x=13 | | 0.3/n=4.75/14.25 |